2008
DOI: 10.1007/s10725-008-9299-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of salt and alkali stresses on growth, osmotic adjustment and ionic balance of an alkali-resistant halophyte Suaeda glauca (Bge.)

Abstract: Effects of salt and alkali stresses on growth, osmotic adjustment and ionic balance of Suaeda glauca (Bge.), an alkali-resistant succulent halophyte, were compared. The results showed that alkali stress clearly inhibited the growth of S. glauca. Moreover, the concentrations of Na + and K + both increased with increasing salinity under both stresses, suggesting no competitive inhibition between absorptions of Na + and K + . The mechanism underlying osmotic adjustment during salt stress was similar to alkali str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
187
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 27 publications
14
187
4
Order By: Relevance
“…Although NO 3 -uptake is promoted by K + in glycophytes, NO 3 -uptake and transport to shoots were promoted by Na + in the Na-loving plants dwarf glasswort and Swiss chard, which indicates quite a different mechanism of NO 3 -uptake between Na-loving plants and glycophytes. Yang et al (2008) reported that a high external Na + increases uptake of anions such as NO 3 -, dihydrogen phosphate ion (H 2 PO 4 -), Sulfate ion (SO 4 -) and chloride ion (Cl -) in Suaeda glauca (Bge.) to maintain charge balance, which supports our results.…”
Section: Effect Of Increasing Na/k Ratio In Solution On Water Uptake mentioning
confidence: 99%
“…Although NO 3 -uptake is promoted by K + in glycophytes, NO 3 -uptake and transport to shoots were promoted by Na + in the Na-loving plants dwarf glasswort and Swiss chard, which indicates quite a different mechanism of NO 3 -uptake between Na-loving plants and glycophytes. Yang et al (2008) reported that a high external Na + increases uptake of anions such as NO 3 -, dihydrogen phosphate ion (H 2 PO 4 -), Sulfate ion (SO 4 -) and chloride ion (Cl -) in Suaeda glauca (Bge.) to maintain charge balance, which supports our results.…”
Section: Effect Of Increasing Na/k Ratio In Solution On Water Uptake mentioning
confidence: 99%
“…Increments of Na + and decrements of K + have been commonly observed in other plant species, not only with increasing salinity but also with increasing pH values (De Lacerda et al 2003). Such responses induced by salinity or alkalinity have been attributed to the competition between Na + and K + (Munns 2002 Yang et al (2008). The phenomenon might be due to the transfer of K + from roots to shoots (Franklin and Zwiazek 2004).…”
mentioning
confidence: 94%
“…More than 23% of irrigated lands have been salinized (Tanji 1990) and its adverse effect is increasing (Ghanem et al 2008). Excessive sodium chloride (NaCl), a major salt in these lands, causes many types of stress symptoms in plants, such as potassium (K) deficiency (Dodd et al 2010;Fraile-Escanciano et al 2010) and osmotic stress (Yang et al 2008). Therefore, preventing crop yield reductions in salinized areas is one of the solutions to avoid a food crisis while the world population is rising.…”
Section: Introductionmentioning
confidence: 99%
“…Positive physiological responses to Na for dry matter production such as co-transport of pyruvic acid (Furumoto et al 2011) and osmotic adjustment (Yang et al 2008) have been reported, but little is known for chenopodiaceous halophytes about mechanisms by which dry matter production is protected against salinized conditions. This study focused on the anti-oxidative response system (ARS) in chenopodiaceous halophyte under salinity conditions.…”
Section: Introductionmentioning
confidence: 99%